RISK FINANCING TECHNIQUES AND SAFETY CULTURE OF ROAD CONSTRUCTION COMPANIES IN EKITI STATE, NIGERIA. - Oluwaleye, Taiwo Olarinre; ADULOJU, Sunday Adekunle (Annals of Spiru Haret University. Economic Series, 2023)
This study explores the effects of risk financing techniques on the safety culture among selected road construction companies in Ado-Ekiti, Nigeria. The study engaged a descriptive survey research design. The population of the study comprises all twenty-eight (28) indigenous road construction companies in Ekiti State out of which seven road construction companies were purposively chosen for the study. A total of 130 copies of a structured questionnaire were dispersed among the respondents to gather data for this study, out of which 118 which represent a 90.6% response rate was found useful for analysis. Descriptive and inferential statistics were used for data analysis. The regression results from the structural equation model revealed that Risk retention has a significant influence on the safety culture with estimates .143(P= .015< .05) while the risk transfer technique recorded an estimate -.002(P=.987>.05) indicating a negative insignificant relationship with the safety culture of road construction companies in Ekiti State, Nigeria. Finally, this study confirms that risk financing techniques hold a negative significant joint influence on the safety culture of road construction companies in the metropolis of Ado, Ekiti State based on reported estimates -.591and (P =***< .05). Therefore, the researcher recommends that road contractors should be meticulous about the appropriate risk financing techniques that will aid safety culture.